Movimento X0 em crianças com implante coclear: evidência para défice sintático em casos de input tardio - Costa, João; Moita, Mara (Revista da Associação Portuguesa de Linguística, 2016)
Orally trained hearing impaired children with hearing aids and cochlear implants show general syntactic deficit in constructions involving movement (passives, wh-questions and relative clauses) as a result of their late exposure to linguistic input (Friedmann & Szterman, 2006). In this paper, we explore XP movement in wh-questions and X0 movement in verbal answers and in clitic production in cochlear implanted children’s spontaneous speech. The results show that these children have no problems with wh- movement but show difficulties with X0 movement, revealing a possible difficulty with a type of movement that takes place at the PF interface.